Metabolomics reveals the effect of vacuum packaging combined with moderate-temperature preservation on quality changes of tender ginger - Ying-Ying Jing; Fan-Bing Meng; Zhen-Yu Peng; Qing-Zhou Li; Ya-Ting Lei; Yun-Cheng Li (Food Chemistry: X)
Tender ginger is often used a fresh vegetable but hard to storage due to the delicate skin, high moisture content and prone to spoilage. In order to develop suitable preservation technology for tender ginger, the effects of vacuum packaging combined with different preservation temperatures (20–25 °C room temperature, 4 °C and 10 °C) on tender ginger shelf life were investigated. The results indicated that vacuum packaging combined with 4 °C (VP4) preservation could easily cause cold damage and postharvest physiological fluctuations. Vacuum packaging combined with 10 °C (VP10) inhibited moisture loss and physiological activities. Metabolomics analysis revealed 169 metabolites significantly differential regulated during VP10 preservation. The characteristic metabolites were primarily associated with amino acid, lipid and nucleotide metabolism. The metabolic pathways mainly involved linoleic acid metabolism; alanine, aspartate and glutamate metabolism; and purine metabolism. The above results indicated that VP10 effectively extended the preservation period of tender ginger with less damage.